Comparative Analysis on Portrayals of Sri Lanka Civil War and People through Newspaper and Political Cartoons - Poongulaly, S. (My University, 2014)
The mass media are diversified media technologies that are intended to reach a large audience by mass communication. The technology through which its communication takes place varies. The medium developed by people to disseminate message to inform, persuade, and entertain people. We can divide the medium as electronic and print media. Newspaper is a publication containing news, information and advertising usually printed on low cost paper called news print. Editorials, headlines, advertisement, obituaries, vacancies, cinema tips, and cartoons, etc.… are the property of each and every newspaper. According to that this study explores about the Comparative analysis on the portrayal of Sri Lankan civil war and people through Newspaper political cartoons. A cartoon is a form of two dimensional illustrated visual arts. The cartoon is containing a political or social message which usually relates to current events or personalities. Political cartoons are art forms portraying government programs, policies, and personalities, in humor ways. For the analysis the researcher has chosen two week – end Newspaper from different languages in the period of final battle (January 2009 – May 2009). Thinakkural (Tamil), Lankadeepa (Sinhala), week – end Newspapers were chosen for this study. From each Newspaper twenty-two cartoons were selected for this analysis. To find out the two languages of Newspaper political cartoons portrayed the Sri Lankan civil war and people in the period od final battle, to explore cartoons published in the selected Sinhala newspaper give more space for government than that of the selected Tamil newspaper give more space regarding Sri Lankan civil war and Tamil people from January 2009 to May 2009, and to explore the cartoonist from both sides mostly used symbols to depict the civil war and people, for that this study has chosen the content analysis method and semiological method. Under the eight categories these cartoons were analyzed. Such as, war theme, use of symbols, portrayal of single or group characters, using less or more text, denotation and cannotation meaning. The conclusion drawn from this analysis is the Tamil newspaper portrayed the civil war mostly while the Sinhala newspaper is portraying another issue. In that case the researcher has found 19 cartoons from Tamil newspaper have portrayed the civil war meanwhile only 09 cartoons have portrayed the civil war in Sinhala newspaper. Further the both cartoonists convey their message by using symbols.
Keywords: Portrayal; Political Cartoons; Sri Lankan Civil war; People; Newspapers